Feeling betrayed the roots of Muslim anger at America - Kull, Steven (Washington, D.C. Brookings Institution Press, 2011)
"Explores the depth of anti-Americanism felt by Muslim populations in the Middle East and South Asia by reporting on opinions expressed during focus group sessions and in-depth surveys over several years, complemented by data from Gallup polls, World Values Survey, and Arab Barometer"--Provided by publisher.
Introduction : America, radical Islamist groups, and the Muslim people -- The scope of Muslim anger and support for violent anti-American groups -- The narrative of oppression and betrayal and the inner clash of civilizations -- The United States as coercively dominating the Muslim world -- The United States as hostile to Islam -- U.S. support for Israel -- The United States as undermining democracy -- Views of Al Qaeda and other radical Islamists -- What do Muslims want? -- What the United States can do.
Keywords: Anti-Americanism -- Islamic countries; United States -- Relations -- Islamic countries; Islamic countries -- Relations -- United States